Legal ensuring of forensic activity: modern aspect - Ostropilets, Vasyl (Archives of Criminology and Forensic Sciences, 2020)
Forensic activity at the current stage of its development is a set of specialized knowledge and procedural rules that govern legal relations related to the appointment and conduct of forensic examinations. The effectiveness of forensic activity depends on a variety of factors: regulatory and legal support, technical equipment and the level of specialized knowledge of each forensic expert. In our opinion, the mechanism of legal regulation of forensic activity is a process of correspondence with the norms of substantive and procedural law in regularized activity of an expert who conducts research on objects in accordance with certain standards. Legal ensuring of forensic activity should be considered through the prism of the terms “examination” and “expert”, which today give a clear picture of the forensic activity in general. After all, forensic activitiy ensuring is implemented through the work of an expert, by his performing an independent, objective, qualified examination. Based on the above, we believe that, firstly, there is an urgent need for accelerated changes in legal ensuring of forensic science, as it will contribute to the creation of optimal conditions for successful professional activity and increase the level of expert ensuring of justice in the country. Secondly, it is essential to introduce into legislation the provision on the status of a private forensic expert. In our opinion, this innovation may stipulate the following: “Forensic examination may be entrusted to: employees of state specialized institutions of forensic examinations; private experts who are engaged in forensic activities on the basis of a license and who have obtained the relevant qualification”. Thirdly, based on international experience, to develop an effective mechanism of relations between the subjects who implement forensic activities in order to avoid (minimize) contradictions and conflicts between representatives of state specialized institutions of forensic